ANALISIS ERITROSIT, LEUKOSIT, DAN HEMOGLOBIN KELINCI PADA UJI MATERI STAINLESS STEEL AISI 316L DAN POLIETILEN UHMWPE - Vebry Tribianto; Koen Praseno; K Kasiyati (Jurnal Akademika Biologi, 2014)
The research of the bone and an artificial hip joint using the non-import material dimensions of the Indonesian until now has not been done. Test about the effect of implantation of these materials for health conditions need to be conducted on animal models, such as the rabbit before it is applied directly in humans. This study aims to determine the number of erythrocytes, leukocytes, and hemoglobin rabbits after implantation of AISI 316L stainless steel and polyethylene UHMWPE implants as well as knowing the material that is safe for the body and can be used for artificial hip joint (hip joint replacement). This study compares the So: rabbit is not given implantation of stainless steel AISI 316L with Si: rabbits were implanted stainless steel AISI 316L, as well as comparing Po: rabbit is not given implantation polyethylene UHMWPE with Pi: rabbits were implanted polyethylene UHMWPE. The study was conducted over 10 weeks. Parameters measured were hemoglobin levels, erythrocyte count, leukocyte count, the body weight and feed intake, then the data were analyzed using T test with SAS procedures at 95% significance level. The results showed that an increase in hemoglobin levels in rabbits with implantation of stainless steel AISI 316L and also polyethylene UHMWPE implantation rabbit, but still within the normal range. The number of erythrocytes and leukocytes of rabbits treated stainless steel AISI 316L implants and implantation treatment of polyethylene UHMWPE rabbit were not significant. It can be concluded that the AISI 316L stainless steel and polyethylene UHMWPE implant material could be safe for the body. Keywords: rabbit, stainless steel AISI 316L, polyethylene UHMWPE